FORENSIC LINGUISTIC ANALYSIS OF DYSPHEMISTIC EXPRESSIONS IN SOCIAL MEDIA DISCOURSE TARGETING PRESIDENT JOKO WIDODO - Dheni Budiman; Dadang Sudana; R. Dian Dia-an Muniroh; Ruswan Dallyono; Agus Syahid (University of Kuningan, 2025)
Social media constitutes a public space for expressing ideas and opinions; therefore, it must be used wisely by its users. Many social media users commit legal violations, such as employing dysphemism (abusive language) toward individuals or groups, including President Joko Widodo during his term of office. This study aims to describe the lexical meanings that emerge in dysphemistic expressions, the purposes of dysphemism, and the legal impact of dysphemism on social media targeting President Joko Widodo. The method employed in this study is a descriptive-analytical method focusing on dysphemism directed at President Joko Widodo on social media. The results indicate that: (1) the lexical meanings that emerge can be classified into eight categories; (2) the purposes of dysphemism toward President Joko Widodo on social media include expressions of hatred, insult, defamation, threats, and the degradation of the dignity and honour of the head of state; and (3) the legal impact of dysphemism on social media targeting President Joko Widodo consists of court verdicts imposed on defendants who are proven to have uttered dysphemistic expressions on social media.